(untitled) (Management and Connections Journal, 2022)
The objective of this presented work was to investigate how the consumer’s contentment with banking services, in different generations (young vs. Mature consumers), differs itself, considering the attributes that shape the perceived value (reputation, service’s quality, convenience and monetary sacrifice). Were conducted analysis of two bank clients as samples: 251 respondents from 18 to 30 years old (young) and 267 above 50 years old (mature consumers), through the characterization of the presenting sample, descriptive statistics, variety’s analysis, rate’s difference test and multivariate linear regression. The results pointed rate differences between the public and all the values perception’s construct regarding the contentment, were statistically positives and considerable. The construct’s interaction between young and mature consumers through the multiple linear decrease indicated that only quality of service was remarkable, in both cases.